Efficacy of dioctahedral smectite in infants with acute diarrhea: a double blind randomized controlled trial - A. A. Made Widiasa; Soetjiningsih Soetjiningsih; Putu Gede Karyana (Indonesian Pediatric Society, 2009)
Background Acute diarrhea is a sudden diarrhea which lasts lessthan seven days on babies and children. The standard treatmentby WHO in managing acute diarrhea is still not satisfactory forparents whose infants and children suffering from the disease.Dioctahedral smectite is expected to decrease the volume,frequency, and duration of diarrhea.Objective To assess the clinical effects of dioctahedral smectite ininfants with acute diarrhea.Methods A double-blind, randomized clinical controlled trial wasperformed on six to 12 months-old infants who were hospitalizedin Sanglah Hospital, Denpasar due to acute diarrhea .The subjectswere divided into two groups. The treatment group was givenstandard management with adjuvant dioctahedral smectitewhile and control group was given standard management withplacebo.Results From 68 infants enrolled in this study, the mean durationof diarrhea was significantly shorter in treatment group comparedto placebo group [39.03 hours (SD 2.03) vs 70.58 hours (SD3.78), mean difference 31.6 (95% CI 22.90 to 40.19), P=0.001].The RRR was 50%, and ARR was 29%. Kaplan-Meier survivalanalysis showed that duration of acute diarrhea was shorter intreatment group [36 hours (SD 1.7) versus 72 hours (SD 4.18),mean difference 36.0 (95% CI 21.81 to 50.19), log rank test,P<0.0001]. In multivariate Cox regression analysis, it was foundthat dioctahedral smectite influenced the duration of diarrheain infants with acute diarrhea [OR 4.403 (95% CI 2.39 to 8.12),P<O.OOOl].Conclusion Dioctahedral smectite can shorten the duration ofacute diarrhea.